(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In today’s corporate environment, the presence of dissatisfaction, differences, and discontent among employees significantly impacts the overall functioning. Within organizations, there exist two distinct dimensions of polities: one focused on positive growth and development, while the other revolves around personal and group gains. The latter, commonly known as politics, operates at an informal and unofficial level, often resulting in detrimental effects and hindering organizational progress. Numerous variables play a significant role in shaping the organizational culture, growth, and development. To delve into these aspects, researchers primarily rely on qualitative research methods, engaging in personal interviews and administering questionnaires to employees across different levels within various organizations. These interactions aim to gain insights into sensitive topics such as organizational politics and development.